A systematic review of lived experiences of people with polycystic ovary syndrome highlights the need for holistic care and co-creation of educational resources - Lau, Gar Mun; Elghobashy, Mirna; Thanki, Mansi; Ibegbulam, Shirley; Latthe, Pallavi; Gillett, Caroline D. T.; O’Reilly, Michael W.; Arlt, Wiebke; Lindenmeyer, Antje; Kempegowda, Punith; , PCOS SEva Working Group (Frontiers in Endocrinology, 2022)
Introduction: Polycystic Ovary Syndrome (PCOS)-related literature is mostly dominated by the medical perspective. However, the condition’s lifelong, far-reaching, and multifaceted impacts highlight the importance to gain perspectives from those with PCOS. Therefore, we performed a systematic review to explore the current literature and gaps around the experiences and perceptions of those living with PCOS Method: A comprehensive search of seven electronic databases was conducted between July and October 2021. A total of 34 from 1615 screened articles were included in this systematic review and subsequently coded using NVivo 12 software. The quality of individual studies was assessed by adaptation to the Critical Appraisal Skills Program (CASP) quality assessment tool. Results: Five domains were generated from the data: Signs/Symptoms, Diagnosis, Management, Perceptions, Resources and Improving Outcomes. Dissatisfaction surrounding the experience of diagnosis was common. Concerns surrounded the perceived lack of knowledge from healthcare professionals and delays in diagnosis. Individual studies on adults and adolescents shared similar feelings. The consensus was found to be that current management was vague and generalised. Symptoms such as hirsutism, obesity, and irregular menstruation challenge personal and societal expectations of femininity. Online PCOS resources are popular amongst those with PCOS but most of them lack evidence. A call for more culturally specific resources was found to be common ground amongst those with PCOS. Conclusion: Overall dissatisfaction amongst adults and adolescents regarding their diagnostic journey of PCOS. Tailored and culturally specific PCOS advice and management is necessary and can be achieved through the co-creation of resources between healthcare professionals and those with PCOS.